2018
DOI: 10.3390/cancers10030083
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Interplay between Chronic Inflammation, the Microbiome, and Cancer: Understanding Disease Progression and What We Can Do to Prevent It

Abstract: Cancer is a multifaceted condition, in which a senescent cell begins dividing in an irregular manner due to various factors such as DNA damage, growth factors and inflammation. Inflammation is not typically discussed as carcinogenic; however, a significant percentage of cancers arise from chronic microbial infections and damage brought on by chronic inflammation. A hallmark cancer-inducing microbe is Helicobacter pylori and its causation of peptic ulcers and potentially gastric cancer. This review discusses th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 276 publications
(352 reference statements)
1
81
0
4
Order By: Relevance
“…To define specific microbial signatures for BC patients may also have implications for future diagnostic development as well as for therapeutic interventions [98]. …”
Section: Discussionmentioning
confidence: 99%
“…To define specific microbial signatures for BC patients may also have implications for future diagnostic development as well as for therapeutic interventions [98]. …”
Section: Discussionmentioning
confidence: 99%
“…Based on recent studies, the microbiome is a risk factor for BC and an explanation for different responses to therapy (9). The question that arises is "How can microbiome affect BC risk; in which mechanisms they detain or improve different therapeutic approaches; and what are the effects of probiotics on breast cancer management?…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that inflammation and prostatic infection can promote prostate tumorigenesis . A recent population‐based retrospective cohort study in 13,453 patients with ischemic cardio‐ or cerebrovascular disease demonstrates that use of low‐dose aspirin twice or more per week correlates with a lower risk of prostate cancer .…”
Section: Epidemiological Evidence For the Prevention Of Cancer By Aspmentioning
confidence: 99%